Influence of Tear Film Instability on IOL Power Calculation Accuracy - Abshar Ahmad, Jamal Hussain, Nawab Ali Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Accurate intraocular lens (IOL) power calculation is essential for achieving optimal refractive outcomes after cataract surgery. Tear film instability may affect corneal surface regularity and influence the accuracy of biometric measurements used in IOL calculation. Objective: To evaluate the influence of tear film instability on the accuracy of IOL power calculation among patients undergoing cataract surgery. Methods: This was a hospital-based analytical cross-sectional study conducted at Swat Medical Complex Teaching Hospital from April 2022 to April 2023, including 190 patients scheduled for cataract surgery. Results: The mean age of participants was 61.8 ± 9.4 years. Tear film instability was observed in 54.7% of patients. The mean keratometry value was 43.84 ± 1.62 D and the mean calculated IOL power was 21.74 ± 2.56 D. Patients with tear film instability demonstrated greater refractive prediction error (0.58 ± 0.34 D) compared with those with stable tear film (0.32 ± 0.21 D). Good postoperative vision (≥6/12) was achieved in 74.7% of patients. Conclusion: Tear film instability may reduce the accuracy of IOL power calculation by affecting corneal measurements. Preoperative identification and treatment of ocular surface abnormalities may improve the reliability of biometric measurements and enhance refractive outcomes following cataract surgery. Keywords: Intraocular lens power calculation; Tear film instability; Cataract surgery; Keratometry; Ocular surface disease.